Evaluation of 3DTV service using asymmetric view coding based on MPEG-2 - Kalva, Hari; Furht, Borko; Christodoulou, Lakis (My University, 2007)
This paper presents the results of the 3DTV quality evaluation on autostereoscopic displays using asymmetric view coding. Asymmetric view coding encodes the stereo views with different quality. It has been shown that the human visual system is able to compensate for this asymmetric view quality and present a good quality 3D video. Asymmetric video coding can be exploited to reduce the bandwidth requirements for 3DTV services. The key factors that affect the asymmetric video coding are the compression algorithms, the human visual system, and the 3D display. We conducted a subjective evaluation of 3D video with asymmetric view quality and encoded using MPEG-2. We also studied the impact of eye dominance on the perceived quality. We show that asymmetric view coding can be used to reduce the bandwidth requirements of 3DTV services based on MPEG-2 view coding
Keywords: Communication, Networking & Broadcasting; Hardware; Three-dimensional imaging; Three-dimensional display systems; 3-D television; Quality control